2023
DOI: 10.3390/antiox12101824
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Light Exposure Triggers ROS to Downregulate Inflammatory Cytokines Induced by SARS-CoV-2 Spike Protein in Human Cell Culture

Blanche Aguida,
Marie-Marthe Chabi,
Soria Baouz
et al.

Abstract: The leading cause of mortality from SARS-CoV-2 is an exaggerated host immune response, triggering cytokine storms, multiple organ failure and death. Current drug- and vaccine-based therapies are of limited efficacy against novel viral variants. Infrared therapy is a non-invasive and safe method that has proven effective against inflammatory conditions for over 100 years. However, its mechanism of action is poorly understood and has not received widespread acceptance. We herein investigate whether near-infrared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…They are associated with various health problems, including cardiac diseases, brain injury, diabetes, and autoimmune disorders, so reducing inflammation can have significant health benefits. In this Special Issue, Aguida et al [47] reported how near-infrared light influences the balance between pro-and anti-inflammatory cytokines by regulating mitochondrial ROS production. In addition, Song et al [48] demonstrated the antioxidant capacity of Artemisia gmelinii extract (AGE).…”
Section: Anti-inflammatory Effects Of Antioxidantsmentioning
confidence: 99%
“…They are associated with various health problems, including cardiac diseases, brain injury, diabetes, and autoimmune disorders, so reducing inflammation can have significant health benefits. In this Special Issue, Aguida et al [47] reported how near-infrared light influences the balance between pro-and anti-inflammatory cytokines by regulating mitochondrial ROS production. In addition, Song et al [48] demonstrated the antioxidant capacity of Artemisia gmelinii extract (AGE).…”
Section: Anti-inflammatory Effects Of Antioxidantsmentioning
confidence: 99%